Cerebrospinal fluid levels of synaptic and neuronal integrity correlate with gray matter volume and amyloid load in the precuneus of cognitively intact older adults. Issue 1 (20th March 2019) - Schaeverbeke, Jolien; Gille, Benjamin; Adamczuk, Katarzyna; Vanderstichele, Hugo; Chassaing, Emeric; Bruffaerts, Rose; Neyens, Veerle; Stoops, Erik; Tournoy, Jos; Vandenberghe, Rik; Poesen, Koen
Abstract: The main pathophysiological alterations of Alzheimer's disease (AD) include loss of neuronal and synaptic integrity, amyloidogenic processing, and neuroinflammation. Similar alterations can, however, also be observed in cognitively intact older subjects and may prelude the clinical manifestation of AD. The objectives of this prospective cross‐sectional study in a cohort of 38 cognitively intact older adults were twofold: (i) to investigate the latent relationship among cerebrospinal fluid (CSF) biomarkers reflecting the main pathophysiological processes of AD, and (ii) to assess the correlation between these biomarkers and gray matter volume as well as amyloid load. All subjects underwent extensive neuropsychological examinations, CSF sampling, [ 18 F]‐flutemetamol amyloid positron emission tomography, and T1 ‐weighted magnetic resonance imaging. A factor analysis revealed one factor that explained most of the variance in the CSF biomarker dataset clustering t‐tau, α‐synuclein, p‐tau181, neurogranin, BACE1, visinin‐like protein 1, chitinase‐3‐like protein 1 (YKL‐40), Aβ1–40 and Aβ1–38 . Higher scores on this factor correlated with lower gray matter volume and with higher amyloid load in the precuneus. At the level of individual CSF biomarkers, levels of visinin‐like protein 1, neurogranin, BACE1, Aβ1–40, Aβ1–38, and YKL‐40 all correlated inversely with gray matter volume of the precuneus. These findings demonstrate that in cognitively intact older subjects, CSF levels of synaptic and neuronal integrity biomarkers, amyloidogenic processing and measures of innate immunity (YKL‐40) display a latent structure of common variance, which is associated with loss of structural integrity of brain regions implicated in the earliest stages of AD. Open Science Badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript, and for *Preregistration* because the study was pre‐registered at https://osf.io/7qm9t/ . The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found at https://cos.io/our-services/open-science-badges/ . Abstract : The cerebrospinal fluid levels of markers reflecting synaptic and neuronal injury, amyloidogenic processing and neuroinflammation were assessed in 38 cognitively healthy subjects at risk for developing Alzheimer's disease (AD). Our study show that by means of a factor analysis, markers reflecting the above‐mentioned pathophysiological processes ongoing in AD share a common variance correlating with gray matter volume as assessed with structural magnetic resonance imaging and brain amyloid deposition as assessed with amyloid positron emission tomography imaging in regions typically involved early in AD. Aβ, amyloid‐β; BACE1, β‐secretase amyloid precursor protein cleaving enzyme‐1; IL‐6, interleukin‐6; MCP‐1, monocyte chemotactic protein‐1; MIP‐1β, macrophage inflammatory protein‐1β; PET, positron emission tomography; p‐tau, phosphorylated‐tau at threonine 181; t‐tau, total‐tau; VILIP‐1, visinin‐like protein 1; YKL‐40, chitinase‐3‐like protein 1. Open Science: This manuscript was awarded with the Open Materials Badge For more information see: https://cos.io/our-services/open-science-badges/